Vertical structure of tropospheric winds on gas giants - R. K. Scott; T. J. Dunkerton (Geophysical Research Letters)
Abstract Zonal mean zonal velocity profiles from cloud‐tracking observations on Jupiter and Saturn are used to infer latitudinal variations of potential temperature consistent with a shear stable potential vorticity distribution. Immediately below the cloud tops, density stratification is weaker on the poleward and stronger on the equatorward flanks of midlatitude jets, while at greater depth the opposite relation holds. Thermal wind balance then yields the associated vertical shears of midlatitude jets in an altitude range bounded above by the cloud tops and bounded below by the level where the latitudinal gradient of static stability changes sign. The inferred vertical shear below the cloud tops is consistent with existing thermal profiling of the upper troposphere. The sense of the associated mean meridional circulation in the upper troposphere is discussed, and expected magnitudes are given based on existing estimates of the radiative timescale on each planet.